REPRESENTASI KELAS DALAM REALITY SHOW “JIKA AKU MENJADI BURUH KILANG TEBU” - Nasrullah Nasrullah (Jurnal Dakwah Tabligh, 2017)
This work would analyze how is the social class represent in Reality Show “Jika Aku Menjadi Buruh Kilang Tebu”. Beside it, how is the social class constructed and implied to audiens also analyzed in this work. Some aspects that support the domination and hegemony of ruling class will be analyzed in this works. The ideology of ruling class is produced and reproduced by mass media create a power relation among social class in society. This focus is also identified and analyzed in relationship to power relation between lower class and ruling class. The exploitation of working class and creating of pseudo consciousness are the political action, especially in the role of television. Those topics also will be analyzed. Using media studies, social class representation in relation of production, domination, hegemony of ideology, and relation of political economy in this reality show will be identified and analyzed. To analyze of the problems, this works using the thoughts of Marx, Gramsci, Althusser and others of media studies philosophers. Those are the basics of theories to analyze how the upper class’s ideology and its power relation are operated in this reality show. The results of the study indicates thet there are many operation of ideology and power relation to massificates the hegemoni and domination of upper class to lower class in this reality show.